Need some help with simple problem.

"Tyler writes this equation to solve a problem:

3(b - 4) = 9 + 6b,

He divides both sides of the equation by 3 to get

b - 4 = 3 +2b

so he concludes that

b= -7."

Okay, well with my math, I did the divide by 3 on both sides, and got

b-4 = 9+ 6b

-------

3

Not sure if I'm right or not.. anyone.. help please!

Re: Need some help with simple problem.

$\displaystyle 3(b - 4) = 9 + 6b$

Dividing both sides by 3 gives

$\displaystyle \frac{3(b - 4)}{3} = \frac{9 + 6b}{3}$

Which simplifies to

$\displaystyle b - 4 = \frac{9 + 6b}{3}$

and then,

$\displaystyle b - 4 = \frac{9 }{3}+ \frac{ 6b}{3}$

$\displaystyle b - 4 = 3+ 2b$

continue...

Re: Need some help with simple problem.

Quote:

Originally Posted by

**pickslides** $\displaystyle 3(b - 4) = 9 + 6b$

Dividing both sides by 3 gives

$\displaystyle \frac{3(b - 4)}{3} = \frac{9 + 6b}{3}$

Which simplifies to

$\displaystyle b - 4 = \frac{9 + 6b}{3}$

and then,

$\displaystyle b - 4 = \frac{9 }{3}+ \frac{ 6b}{3}$

$\displaystyle b - 4 = 3+ 2b$

continue...

Oh okay. So the original way "Tyler" did it is correct.

Edit: Actually, he's not correct. The answer is -8, am I correct?

Re: Need some help with simple problem.

$\displaystyle b - 4 = 3+ 2b$

Take 3 from both sides.

$\displaystyle b - 7 = 2b$

Take b from both sides

$\displaystyle - 7 = b$